Allegory or Literal Representation? Indigenous Women in Public Art in Espírito Santo - Kumm, Rosely; Oliveira, Jaqueline Torquatro de; Mello, Júlia (Farol, 2025)
The history of monument representation in public art in Espírito Santo is marked by male figures, tied to a hegemonic discourse shaped by issues of colonization and patriarchy. According to data collected by the Arts Extension and Research Laboratory of the Federal University of Espírito Santo (LEENA/UFES), less than 10% of monuments in Espírito Santo depict women. Among these monuments, two that reference indigenous peoples allow for an assessment of the representation of indigenous women: Mãe-bá (1999) and Fonte do Caju (Fountain of Caju) (1980). Thus, this article investigates these works with the goal of analyzing both their relevance to the preservation of Indigenous culture and identity and questioning the visibility of women, especially those embedded in the culture of Indigenous peoples in the state.
Keywords: public art; Indigenous women; monuments; Espírito Santo culture